Development of marker of homogentisate geranylgeranyl transferase gene of Elaeis species - Mohd Nadzir, Mas Muniroh (2013)
Homogentisate geranylgeranyl transferase (HGGT) is the enzyme that catalyzes the first committed step in tocotrienol biosynthesis. The two oil palm species, Elaeis guineensis and Elaeis oleifera demonstrate high variability in tocotrienol content and thus HGGT gene is a potential candidate for marker development for nutritional rich oil. Five overlapping primers were used to get the contigs of the HGGT gene which were aligned to get the scaffold. The total size of HGGT gene determined from the scaffold was 4,279 the promoter region of the HGGT gene to discriminate between the two species. It was based on single nucleotide polymorphism (SNP) located at the promoter region of E. guineensis and E. oleifera using simple mismatch primer method. Three primers each were designed at eight SNP locations. The forward primers were species-specific where a single nucleotide mismatch was introduced right before the SNP at the 3’ -end. One common reverse primer was designed 150 – 200 bp from the SNP location to be used with the two species-specific forward primers per SNP location. The primers were tested on the specific species (i.e specific primer of E. guineensis using E. guineensis DNA template) and also on the unspecific species. The result showed that the bands produced were brighter when the primers were used with the specific species while faint bands were produced with the unspecific species. Only three primers (1 primer set) were used for screening where the SNP was located at 132 bp from 5’ end of the promoter region. The primer set was chosen based on the intensity of the bands and the presence of an ACGT motif at the SNP location. Thirty seven E. guineensis individuals and 37 E. oleifera individuals were tested and showed that bands were brighter when primers were used with the specific species. Sequencing result of eight individuals showed that the allele was homozygous at the SNP location. All the E. guineensis individuals have conserved ACGT motif at that location. This proves that the mismatch primer could be used to discriminate the species. To see if there are any SNPs that could be associated with the high vitamin E content of E. guineensis, six individuals from different populations were sent for sequencing using overlapping primer method. Four of the individuals have high vitamin E content and two with low vitamin E content. The result showed that the promoter sequence was not highly polymorphic, and no SNP could be bp and 3,851 bp for E. guineensis and E. oleifera, respectively. Alignment to the HGGT amino acid sequence showed that the HGGT gene has large introns of different sizes with E. guineensis having 15 introns whereas E. oleifera with eight introns. There are 11 splice sites with GT/AG being the most prominent. Molecular marker was developed at used to associate with the high vitamin E content. However, one SNP and one indel could be used for fingerprinting to distinguish the Tanzanian population. SNP marker within HGGT proven useful for fingerprinting to differentiate between and within oil palm species.